PENERAPAN AKAD KONVENSIONAL DAN SYARIAH PADA PEMBIAYAAN DI PT. ADIRA FINANCE SYARIAH SATELLIT BALUNG - Abd. ghafur; Nur istianah putri (Finance : Journal of Accounting and Finance, 2023)
This research aims to analyze the application of conventional contracts and sharia contracts applied to financing at PT. Adira Finance Syariah balung. In the current rapid economic era, PT. Adira Finance Syariah operates in the leasing sector where there is an agreement between the two parties, namely between the Company and the consumer, with the provision of rental payments within the agreed agreement time. When paying the rent, conventional and sharia leasing is applied. There is a comparison between financing conventional contracts and sharia contracts. In conventional leasing, a contract with an interest system is used as the objective. Meanwhile, in sharia leasing, a murabahah (sale and purchase) contract is used, whereas the advantages of the sharia contract itself are in terms of profit margin. The application of these two contracts is to further understand the business leases that are applied in leasing companies. The purpose of writing this report is to determine the differences between conventional leasing contracts and sharia leasing contracts. The type of data the author uses is secondary or external data. This research uses a qualitative descriptive research method.